1996
DOI: 10.1029/96gl02071
|View full text |Cite
|
Sign up to set email alerts
|

Molecular excitation in sprites

Abstract: We have determined the molecular internal energy distribution in the N2 B³IIg state from the fluorescence measured during the observations of sprites during 1995. Spectrally resolved data from two different instruments and three different sprites are compared with theoretical spectra to obtain excited state vibrational distributions. Energy dependent electron excitation cross‐sections and laboratory data were used to estimate the energies of electrons producing the red sprite radiance. Implications for chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 15 publications
5
56
0
Order By: Relevance
“…[40] Due to the strong absorption of the 762 nm emissions by O 2 below 60 km, the sprite emissions in this band were much reduced in the sprite spectra measured from the ground [Mende et al, 1995;Green et al, 1996;Hampton et al, 1996;Kanmae et al, 2007Kanmae et al, , 2010. However, in the ISUAL 762 nm sprites, in addition to the sprite emissions, the imager frames in Figures 6a-6e contain much stronger emissions from the parent lightning in this band.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40] Due to the strong absorption of the 762 nm emissions by O 2 below 60 km, the sprite emissions in this band were much reduced in the sprite spectra measured from the ground [Mende et al, 1995;Green et al, 1996;Hampton et al, 1996;Kanmae et al, 2007Kanmae et al, , 2010. However, in the ISUAL 762 nm sprites, in addition to the sprite emissions, the imager frames in Figures 6a-6e contain much stronger emissions from the parent lightning in this band.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of this study is to understand the spectroscopic content of the ISUAL sprites taken through a narrowband 762 nm filter, taking into account the various coupled physical processes producing optical emissions. It is expected that for spaceborne observations, the sprite emissions in the 762 nm range will primarily come from the sprite body due to strong absorption in the O 2 atmospheric band (O 2 atm) by O 2 below 60 km, as indicated by various ground-based measured sprite spectra [Mende et al, 1995;Green et al, 1996;Hampton et al, 1996;Kanmae et al, 2007Kanmae et al, , 2010. The 762 nm filter for observing sprites has been proposed for several spacecraft projects, such as it was used in the narrowband spectroscopic cameras of the SPRITE-SAT project [Takahashi et al, 2010] and in the micro cameras and photometers of the upcoming TARANIS project [Blanc and Lefeuvre, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…The temporal resolution used by both groups was of 33 ms given by standard video recording at 30 frames per second. The work by Green et al [1996] focused on the analysis of the results previously reported by Hampton et al [1996] and Mende et al [1995]. The results by Green et al [1996] were the first to discuss the possible nature of the different molecular excitation mechanisms present in sprites and to provide some quantitative analysis on the relative populations of N 2 (B 3 P g ) vibrational levels up to v = 10 derived from the data reported by Mende et al [1995] and Hampton et al [1996].…”
Section: Introductionmentioning
confidence: 99%
“…The work by Green et al [1996] focused on the analysis of the results previously reported by Hampton et al [1996] and Mende et al [1995]. The results by Green et al [1996] were the first to discuss the possible nature of the different molecular excitation mechanisms present in sprites and to provide some quantitative analysis on the relative populations of N 2 (B 3 P g ) vibrational levels up to v = 10 derived from the data reported by Mende et al [1995] and Hampton et al [1996]. However, the results concerning the emission from N 2 first positive system presented by Mende et al [1995] and Hampton et al [1996] mostly covered Dv = 2, 3 and 4, and only a few transitions from the Dv = 1 bands that allowed little experimental information on the v = 0 and v = 1 relative populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation